Atrial fibrillation risk factor burden and disease onset across age decades. (25th November 2020) - Morseth, B; Geelhoed, B; Linneberg, A; Soderberg, S; Johansson, L; Kuulasmaa, K; Salomaa, V; Niiranen, T; Iacoviello, L; Loechen, M.L; Schnabel, R.B
Abstract: Background: Although a number of risk factors have been associated with the progression of atrial fibrillation (AF), there is limited knowledge of their relevance for AF in relation to age. Purpose: We examined whether the association between modifiable risk factors and AF differed between age decades. Methods: Data were derived from five European cohorts from Denmark, Finland, Italy, Sweden, and Norway. In total, 66 951 individuals (49.1% men) aged ≥40 years (mean baseline age 53.5 years) and without prevalent AF were followed for incident AF, with the follow-up truncated at 10 years. Data on risk factors (body mass index [BMI], hypertension [systolic blood pressure ≥140 mmHg and/or use of antihypertensive medication], diabetes mellitus, myocardial infarction [MI] event before baseline examinations, daily smoking, and alcohol consumption) were available from the baseline examinations. Stratification into age decades was based on age at baseline examination. Furthermore, the participants were followed for events of stroke or mortality after AF diagnosis. Mortality, stroke, and AF outcomes were derived from national registers and hospital discharge registers. All analyses were adjusted for AF risk factors. Results: The incidence of AF increased from 0.9 per 1000 person-years at the age of 40 to <50, to 17.7 at the age of ≥70 years. Multivariable-adjusted Cox models showed that BMI, hypertension, alcohol consumption, and history of MI were associated with increased risk of AF across age decades (p<0.05). Of these, the risk of AF associated with BMI and an MI event before baseline examinations differed across age decades. For each 5 units increase in BMI, risk of AF increased with 40% (95% confidence interval 17–68%) at the age of 40 to <50, falling to 17% (6–29%) at the age of ≥70 years (p=0.08 for difference between age decades 40 to <50 and ≥70). Participants with a history of MI showed decreased risk of AF with ageing, from a hazard ratio (HR) of 5.53 (2.85–10.73) in the 40 to <50 age group to a HR of 1.41 (1.11–1.79) at the age of ≥70 (p<0.001). Daily smoking and prevalent diabetes mellitus were in general not associated with AF. The multivariable-adjusted associations between new-onset AF and the succeeding risk of stroke and mortality increased with age, showing a 1.6 to 2.6-fold increase in risk of death at ages ≥60 years and two-fold increased risk of stroke in participants aged ≥70 years (p≤0.001). Conclusion: The relative importance of modifiable risk factors on incident AF do not vary across age decades, with a few exceptions; BMI and a history of MI were stronger risk factors for AF at younger ages. Thus, preventive measures should target risk factors rigorously, in particular obesity. New-onset AF was associated with increased risk of stroke and mortality only at older ages, emphasizing the importance of adequate patient management in the older and oldest old. Funding Acknowledgement: Type of funding source: None